PENGARUH UKURAN PERUSAHAAN, UKURAN KAP DAN OPINI AUDIT TERHADAP MANAJEMEN LABA - Pohan, Erlina Sari; Aprilliadi, Teddy; Nurelvini, Abellia (LPPM Universitas Bina Bangsa, 2023)
This study aims to examine whether there is an influence of firm size, size of the Public Accounting Firm (KAP) and auditor's opinion on earnings management activities in chemical sub-sector companies. The population in this study are chemical sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The number of samples in this study were 10 companies with the sampling technique using purposive sampling method. The research method used is quantitative with data sources in the form of secondary data. Methods of data analysis using linear regression analysis with SPSS version 25. The results of this study provide empirical evidence that the variable firm size, size of the Public Accounting Firm (KAP) and auditor opinion have no effect on earnings management